Giant Mediastinal Mass in A 3-year-old Boy, A Rare Presentation of Neurofibromatosis Type I - karami, hossein; naderisorki, mohammad; ghasemi, maryam; taheri, amirmasoud; rostamkolaie, faria (Iranian Journal of Child Neurology, 2021)
Neurofibromatosis type 1 (NF1) is an autosomal dominant disease diagnosed with presentation of café-au-lait macules, Skinfold freckling, iris Lisch nodules, neurofibromas, osseous lesion and Optic gliomas. Mediastinal mass as first presentation of NF1 is very rare and its frequency is about 2.7%. here we present a rare case of NF1 in a 3-year-old boy admitted with respiratory distress and superior vena cava syndrome.